Composition and characteristics of flavoured milk prepared using tagatose as a substitute of sucrose - Patel, Akashamrut M; Mehta, Bhavbhuti M; Aparnathi, KD; Hati, Subrota (Indian Journal of Dairy Science, 2022)
In a present era of reduction in consumption of sucrose, finding an ideal alternative of sucrose for application in sweetened food products serves as a boon. However, to find an ideal substitute of sucrose remained a destined dream. Fortunately, now tagatose is emerging as highly potential substitute of sucrose for use as a sweetener in food products. In the present study suitability of tagatose was evaluated as a sweetener in flavoured milk. The findings of the study suggested that flavoured milk prepared by partial (50%) substitution of sucrose was well acceptable in sensory evaluation and that prepared by complete substitution of sucrose using blend of tagatose along with fructose as an adjunct sweeter was highly acceptable. Tagatose was able to substitute sucrose in flavoured milk without any change in the process parameters. Proximate composition, physicochemical properties and microbial counts of the sucrose substituted flavoured milk were almost similar to that prepared by using sucrose as a sweetener. Shelf life of the sucrose substituted flavoured milk was also similar to corresponding flavoured milk prepared by using sucrose as a sweetener.